Fenomena Kondisi Sanitasi Air Bersih di Rusunawa Tanggalrejo Kecamatan Tempuran Kabupaten Magelang - Mahendradi Mahendradi; Ardiyansah Ardiyansah (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2020)
In 2012, Indonesia ranked the worst in the availability of clean water and suitable for consumption in Southeast Asia. There are various efforts in improving human health, one of which is by providing basic sanitation. Basic sanitation efforts in the community are carried out through various means including the provision of clean water, healthy latrines, waste management and sewerage. The conditions of households that have the potential to experience a clean water crisis include the area of ​​flats. This study aims to provide an overview of the condition of clean water sanitation in Rusunawa Tanggulrejo, Magelang Regency. This research uses a quantitative method with a survey approach that is processed using statistics. The results found that drainage conditions, sewage disposal conditions, clean water conditions, and clean water flow conditions in Rusunawa Tanggulrejo are categorized as good based on the number of respondents' average responses to these conditions, but in practice there are some things that need to be improved, including the condition of clean water sources for residents, clean water sanitation checks, and health services provided to residents of Rusunawa. Keywords: Strategy, Increasing the Predicate of Disadvantaged Areas, Pandeglang Regency